Sialic acids regulate microvessel permeability, revealed by novel in vivo studies of endothelial glycocalyx structure and function. (1st August 2017) - Betteridge, Kai B.; Arkill, Kenton P.; Neal, Christopher R.; Harper, Steven J.; Foster, Rebecca R.; Satchell, Simon C.; Bates, David O.; Salmon, Andrew H. J.
Abstract : Key points: We have developed novel techniques for paired, direct, real‐time in vivo quantification of endothelial glycocalyx structure and associated microvessel permeability. Commonly used imaging and analysis techniques yield measurements of endothelial glycocalyx depth that vary by over an order of magnitude within the same vessel. The anatomical distance between maximal glycocalyx label and maximal endothelial cell plasma membrane label provides the most sensitive and reliable measure of endothelial glycocalyx depth. Sialic acid residues of the endothelial glycocalyx regulate glycocalyx structure and microvessel permeability to both water and albumin. Abstract: The endothelial glycocalyx forms a continuous coat over the luminal surface of all vessels, and regulates multiple vascular functions. The contribution of individual components of the endothelial glycocalyx to one critical vascular function, microvascular permeability, remains unclear. We developed novel, real‐time, paired methodologies to study the contribution of sialic acids within the endothelial glycocalyx to the structural and functional permeability properties of the same microvessel in vivo . Single perfused rat mesenteric microvessels were perfused with fluorescent endothelial cell membrane and glycocalyx labels, and imaged with confocal microscopy. A broad range of glycocalyx depth measurements (0.17–3.02 μm) were obtained with different labels, imaging techniques and analysis methods. The distance between peak cell membrane and peak glycocalyx label provided the most reliable measure of endothelial glycocalyx anatomy, correlating with paired, numerically smaller values of endothelial glycocalyx depth (0.078 ± 0.016 μm) from electron micrographs of the same portion of the same vessel. Disruption of sialic acid residues within the endothelial glycocalyx using neuraminidase perfusion decreased endothelial glycocalyx depth and increased apparent solute permeability to albumin in the same vessels in a time‐dependent manner, with changes in all three true vessel wall permeability coefficients (hydraulic conductivity, reflection coefficient and diffusive solute permeability). These novel technologies expand the range of techniques that permit direct studies of the structure of the endothelial glycocalyx and dependent microvascular functions in vivo, and demonstrate that sialic acid residues within the endothelial glycocalyx are critical regulators of microvascular permeability to both water and albumin. Key points: We have developed novel techniques for paired, direct, real‐time in vivo quantification of endothelial glycocalyx structure and associated microvessel permeability. Commonly used imaging and analysis techniques yield measurements of endothelial glycocalyx depth that vary by over an order of magnitude within the same vessel. The anatomical distance between maximal glycocalyx label and maximal endothelial cell plasma membrane label provides the most sensitive and reliable measure of endothelial glycocalyx depth. Sialic acid residues of the endothelial glycocalyx regulate glycocalyx structure and microvessel permeability to both water and albumin.